2013
DOI: 10.1108/14439881311314694
|View full text |Cite
|
Sign up to set email alerts
|

Using narratives to understand progress in youth alcohol and other drug treatment

Abstract: Purpose: This paper aims to illustrate how narrative research techniques can be employed to promote greater understanding of young people's experiences of progress in residential alcohol and other drug treatment. Design/methodology/approach: Narrative inquiry is used to explore client understandings of what characterises progress in treatment for young people attending a residential detoxification and a residential rehabilitation service in Perth, Western Australia. This article focuses on stories of progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 62 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…The findings show that many of the young people in the study have experienced significant external pressure to stop using drugs and undergo treatment, consistent with previous research (Battjes et al, 2003; Hugo et al, 2021; Wilson & Saggers, 2013). However, these interventions did not give the desired results due to a lack of autonomous motivation and a social environment that did not support this.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings show that many of the young people in the study have experienced significant external pressure to stop using drugs and undergo treatment, consistent with previous research (Battjes et al, 2003; Hugo et al, 2021; Wilson & Saggers, 2013). However, these interventions did not give the desired results due to a lack of autonomous motivation and a social environment that did not support this.…”
Section: Discussionsupporting
confidence: 90%
“…Young people often begin treatment due to pressure and demands from parents and professionals, and commonly lack intrinsic motivation to change their drug use, at least initially (Battjes et al, 2003; Hugo et al, 2021; Wilson & Saggers, 2013). In line with this, many of the participants in the study reported a high degree of external pressure to stop using drugs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The client’s change experience progressed from a state of painful self-focus to a (eventual) positive other focus , exploring and forming new commitments instead of gambling. The reported change process bears resemblance to the narratives of people who recover from addiction, and whose stories change from that of exclusion and disconnection to that of opportunity, inclusion, and possibility (Wilson, Saggers, & Wildy, 2013). As seen in the phase-based results, the client’s experience of change was initially self-acceptance and relationship building, which took place through learning about trauma and feeling normalized.…”
Section: Discussionmentioning
confidence: 84%